2000
DOI: 10.1143/jjap.39.l887
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Nanotube Tip for Highly-Reproducible Imaging of Deoxyribonucleic Acid Helical Turns by Noncontact Atomic Force Microscopy

Abstract: A carbon nanotube (CNT) was used as a tip for a noncontact-mode atomic force microscope (NC-AFM). A CNT tip was attached to an Au/Si tip by a well-controlled procedure in a scanning-electron-microscope (SEM) chamber. The NC-AFM with the CNT tip produced highly reproducible images of right-handed helical turns of linear deoxyribonucleic acid (DNA) with a spacing of 3.5 ±1.0 nm. The full-width at half-maximum (FWHM) of the cross section of DNA measured was 3.1 ±0.6 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Techniques for accomplishing this include: (1) bonding a CNT to the apex of a commercially available tip using an acrylic adhesive; 2 (2) growing a CNT on the apex of a tip using a chemical vapour deposition method; 3,4 and attaching a CNT to the apex of a tip by an electron-beam-induced deposition of amorphous carbon (contaminants) under a scanning electron microscope. 5 -8 The CNT tips thus prepared are used for imaging biological materials 3,8,9 and for CNTs 10 having very high resolution and superb stability with no damage to the sample or CNT tip itself. The CNT tips also have been demonstrated to Ł Correspondence to: Tetsuo Shimizu, Nanotechnology Research Institute-National Institute of Advanced Industrial Science and Technology (NRI-AIST), 1-1-1 Higashi, Tsukuba, Ibaraki 305-8562, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for accomplishing this include: (1) bonding a CNT to the apex of a commercially available tip using an acrylic adhesive; 2 (2) growing a CNT on the apex of a tip using a chemical vapour deposition method; 3,4 and attaching a CNT to the apex of a tip by an electron-beam-induced deposition of amorphous carbon (contaminants) under a scanning electron microscope. 5 -8 The CNT tips thus prepared are used for imaging biological materials 3,8,9 and for CNTs 10 having very high resolution and superb stability with no damage to the sample or CNT tip itself. The CNT tips also have been demonstrated to Ł Correspondence to: Tetsuo Shimizu, Nanotechnology Research Institute-National Institute of Advanced Industrial Science and Technology (NRI-AIST), 1-1-1 Higashi, Tsukuba, Ibaraki 305-8562, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors reported applications of a CNT tip to imaging biological samples (27)(28)(29)(30)(31). The first application was carried out on DNA molecules deposited onto mica surfaces (27,28).…”
mentioning
confidence: 99%
“…The first application was carried out on DNA molecules deposited onto mica surfaces (27,28). The width of the imaged DNA molecules was 7 to 8 nm, in contrast to 12 to 15 nm observed using a standard AFM tip, and detailed structures of two dsDNAs crossed over one another were visualized in air.…”
mentioning
confidence: 99%
“…Carbon nanotube (CNT) is a candidate for ideal mass 1-5 or force [6][7][8][9] sensing devices, due to its extraordinary characteristics. We have recently studied the energy losses of the CNT oscillation, 10,11 and the influence of the viscous fluid to the CNT oscillation at various temperatures toward mass measurement of biological molecules.…”
Section: Introductionmentioning
confidence: 99%